1998
DOI: 10.1136/vr.143.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Welfare of cats in a quarantine cattery

Abstract: The welfare of seven domestic cats housed singly in a quarantine cattery was studied for six months. Behavioural data were obtained with cameras and by time-lapse video recording, and cortisol to creatinine ratios were measured in urine samples collected from litter trays. It took five weeks for the cats to show evidence of adaptation to their new environment. They spent most of the first two weeks concealed in a house on the floor of their cage. As they adapted, they spent less time hiding and more time highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 12 publications
3
40
0
1
Order By: Relevance
“…In both the previous study and this one, contentment was indicated by behaviours such as sitting at the front of the cage, lying on their side while resting or sleeping, friendly behaviour towards humans, normal patterns of feeding, grooming and locomotion, and the absence of defensive or restless behaviour. Of the 250 cats which took part in the larger research project, 38% were rated as Content upon admission, compared to 56% and 6% rated as Anxious and Frustrated, respectively; supporting the notion that entering an animal shelter induces stress in cats (McCune, 1992;Rochlitz et al, 1998a;Rodan, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…In both the previous study and this one, contentment was indicated by behaviours such as sitting at the front of the cage, lying on their side while resting or sleeping, friendly behaviour towards humans, normal patterns of feeding, grooming and locomotion, and the absence of defensive or restless behaviour. Of the 250 cats which took part in the larger research project, 38% were rated as Content upon admission, compared to 56% and 6% rated as Anxious and Frustrated, respectively; supporting the notion that entering an animal shelter induces stress in cats (McCune, 1992;Rochlitz et al, 1998a;Rodan, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Recommendations for environmental enrichment include provision of adequate quantity of space as described in the section on population density. Quality of space is also important, and an optimal cage should include a place to hide, an elevated resting area, feeding and litter areas separated as widely as possible, comfortable bedding, and a scratching surface [40,[45][46][47][48]. Solitary cats in double-sided housing have more control over their environment and are more interactive with strange people than solitary cats in traditional single cages [41].…”
Section: Stress Reduction/environmental Enrichmentmentioning
confidence: 99%
“…First, similar effects sometimes occur in situations known to be aversive; for example, felids spend much time inactive and hidden when exposed to stressors such as translocation (e.g. Carlstead et al, 1993;Rochlitz et al, 1998;Wielebnowski et al, 2002), as do rodents exposed to predation threat (e.g. Dalm et al, 2009).…”
Section: Introductionmentioning
confidence: 99%